THE THORN IN THE FLESH: A PAULINE VIEW OF SUFFERING IN 2 CORINTHIANS 12:7 - Cardona, Christian D.; Woy, Jones Ted Lauda (Klabat Theological Review; Vol 4 No 1 (2024): Klabat Theological ReviewDO - 10.31154/ktr.v4i1.1138.41-52, 2024)
This paper seeks to uncover the spiritual lesson Paul intended to convey through the expression "a thorn in the flesh" in 2 Corinthians 12:7. While much discussion has centered on the nature of this thorn, this study emphasizes its purpose and function within Paul's message. By examining the broader context of 2 Corinthians and focusing specifically on 12:7, the paper aims to reveal the deeper spiritual insights Paul was imparting to his audience. Keywords: Thorn, Flesh, Suffering, Christian.